Recovery following the extra-time period of soccer: practitioner perspectives and applied practices - Field, Adam; David Corr, Liam; James Thompson, Chris; Gonzalez Lucena, Jean Carlos; Sarmento, Hugo; Joseph Naughton, Robert; Edward Brownlee, Thomas; Haines, Matthew; Michael Page, Richard; David Harper, Liam (Biology of Sport, 2022)
Research has demonstrated that the extra-time (ET) period of soccer negatively impacts recovery. However, it is not known to what extent recovery practices are being adapted by practitioners following ET and where gaps exist between research and practice. Therefore, thisstudy explored soccer practitioner perceptions of recovery practices following ET matches. A total of 72 practitioners from across different levels of soccer and several countries completed a bespoke online survey. Inductive content analysis of the responses identified five higher-order themes: ‘conditioning’, ‘player monitoring’, ‘recovery practices’, ‘training’, and ‘future research directions’. Mixed responses were received in relation to whether practitioners condition players in preparation for ET, though 72% allowed players to return to training based on fatigue markers following this additional 30-min period. Sixty-three (88%) practitioners believed that ET delays the time-course of recovery, with 82% highlighting that practices should be adapted following ET compared with a typical 90-min match. Forty-nine practitioners (68%) reduce training loads and intensities for up to 48 hr post ET matches, though training mostly recommences as ‘normal’ at 72 hr. Sixty-three (88%) practitioners believed that more research should be conducted on recovery following ET, with ‘tracking players physiological and physical responses’, ‘nutritional interventions to accelerate recovery’ and ‘changes in acute injury-risk’ being the three areas of research that practitioners ranked as most important. These data suggest practitioners and coaches adjust recovery practices following ET matches compared to 90 min. Further research on the efficacy of recovery strategies following ET matches is required to inform applied practice.